The Emerald handbook of public administration in Latin America - Peters, B. Guy; Alba, Carlos R.; Ramos, Conrado (Emerald Publishing, 2021)
While most scholarship on public administration in Latin America has taken an overtly legal approach, this handbook examines the subject from a political and public management perspective. In so doing, this handbook brings the study of public administration in Latin America more in line with studies conducted in other parts of the world, providing a basis for much more fruitful comparison. The handbook is divided into two parts. The first section contains chapters that explore a range of administrative systems in existence across Latin America, including the major representative types of public administration. The second portion of the book presents comparative examinations of important issues relating to public administration across the region, including accountability, public personnel management, policy coordination and the politics of bureaucracy. In providing an in-depth examination of public administration in contemporary Latin America, this handbook is a vital resource for scholars interested in the fields of public administration in both a Latin American and comparative context, as well as practitioners in government.